Influence of Hearing Aids on the Speech and Language Development of Children with Hearing Loss - Atika Saleem, Hafiza Fatima Rafique, Faiza Mushtaq, Saira Zaman, Asifa Zia, Athar Adnan Uppal (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The World Health Organization (WHO) states that some 466 million people have disabling hearing loss worldwide and that a large proportion of these live in low and middle income countries. A vital tool to help children to hear sounds and speech which is necessary for their speech and language development, is hearing aids to amplify sound. Objective: To assess the impact of hearing aids on the language and speech development of children with hearing loss. Study Design: Observational descriptive study Place and Duration of Study: Hamza Foundation Academy for the Deaf and Audiology Center Lahore from 1st August 2019 to 31st December 2020. Methodology: A self-designed questionnaire was distributed to 50 children aged 2 to 12 years with mild to severe hearing loss. The questionnaire comprised 20 questions assessing speech and language development post-hearing aid use. Results: 6% of the subjects reported a poor quality of life, 56% reported a moderate quality of life, and 38% reported a better quality of life. The research indicates that children with significant hearing loss who use hearing aids experience positive effects on their social, emotional, psychological, and physical health. Conclusion: Children with hearing loss benefit from hearing aids in relation to their language and speech development. Early fitting and consistent use of hearing aids are crucial for maximizing their benefits. These findings underscore the need for early hearing assessments and interventions, as well as the importance of continuous support for children and their families. Keywords: Hearing aids, Hearing loss, Speech development, Language development, Children, Quality of life.